HUBUNGAN KELINCAHAN DENGAN KEMAMPUAN DRIBBLING SEPAKBOLA SISWA EKSTRAKURIKULER SMK NEGERI 7 PEKANBARU - Perez, Albert Yaser; Slamet, Slamet; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study was to reveal about: the relationship of agility with football dribbling skills on extracurricular students of SMK Negeri 7 Pekanbaru. This research belongs to the type of correlational research (Correlation Research). The population of this study was 18 extracurricular students at SMKN Pekanbaru Pekanbaru. This study uses the technique of total sampling (saturated sample), the entire population used as samples. Based on the results of the research conducted on Extracurricular Students in SMK 7 Pekanbaru, it can be concluded that the correlation value or value of r count = 0.597> r table = 0.468. and the results of the significant level of the results of the calculation are known t = 2.974 while t table with dk = n-2 = 18-2 = 16 at the 95% confidence level is 1.746. Thus a conclusion can be drawn that: There is a significant relationship between agility and football dribling skills in Extracurricular Students of SMKN 7 Pekanbaru. Thus a conclusion can be drawn that: There is a significant relationship between agility and football dribling skills in Extracurricular Students at SMK 7 Pekanbaru.Key Words: Agility, Dribbling